In Vivo Studies Suggest that Induction of VanS-Dependent Vancomycin Resistance Requires Binding of the Drug to d-Ala-d-Ala Termini in the Peptidoglycan Cell Wall - Kwun, Min Jung (American Society for Microbiology, 2013)
VanRS two-component regulatory systems are key elements required for the transcriptional activation of inducible vancomycin resistance genes in bacteria, but the precise nature of the ligand signal that activates these systems has remained undefined. Using the resistance system in Streptomyces coelicolor as a model, we have undertaken a series of in vivo studies which indicate that the VanS sensor kinase in VanB-type resistance systems is activated by vancomycin in complex with the d-alanyl-d-alanine (d-Ala-d-Ala) termini of cell wall peptidoglycan (PG) precursors. Complementation of an essential d-Ala-d-Ala ligase activity by constitutive expression of vanA encoding a bifunctional d-Ala-d-Ala and d-alanyl-d-lactate (d-Ala-d-Lac) ligase activity allowed construction of strains that synthesized variable amounts of PG precursors containing d-Ala-d-Ala. Assays quantifying the expression of genes under VanRS control showed that the response to vancomycin in these strains correlated with the abundance of d-Ala-d-Ala-containing PG precursors; strains producing a lower proportion of PG precursors terminating in d-Ala-d-Ala consistently exhibited a lower response to vancomycin. Pretreatment of wild-type cells with vancomycin or teicoplanin to saturate and mask the d-Ala-d-Ala binding sites in nascent PG also blocked the transcriptional response to subsequent vancomycin exposure, and desleucyl vancomycin, a vancomycin analogue incapable of interacting with d-Ala-d-Ala residues, failed to induce van gene expression. Activation of resistance by a vancomycin–d-Ala-d-Ala PG complex predicts a limit to the proportion of PG that can be derived from precursors terminating in d-Ala-d-Lac, a restriction also enforced by the bifunctional activity of the VanA ligase.